Star-formation efficiency at 600Myr of cosmic time. Issue Volume 15:Issue S352(2019) (June 2019) - Stefanon, Mauro; Labbé, Ivo; Bouwens, Rychard; Oesch, Pascal
Abstract: Current observations suggest an accelerated evolution of the cosmic star formation rate density for 8 < z < 10, indicating that galaxy assembly experienced an extremely intense phase during the first ∼600Myr years of cosmic time. We performed a systematic search of ultrabright star-forming galaxies at z ∼ 8 over the COSMOS/UltraVISTA survey, identifying 16 candidate Lyman-break galaxies. The still large uncertainties on the associated volume density do not yet allow us to ascertain whether a different star-formation efficiency (SFE) existed at early cosmic epochs. Leveraging the deepest Spitzer/IRAC data available from the GREATS program over the CANDELS/GOODS fields, we also constructed stacked SEDs of sub- L * LBGs at z ∼ 8. We find extreme nebular line emission (EW0 (Hα) ∼ 1000Å), high specific star-formation rates (∼10/Gyr) and indication of an inverse Balmer break. These results point toward very young ages (<100 Myr), and, combined with measurements at lower redshifts, that the SFE evolved only marginally during the first ∼1.5Gyr of cosmic history.